The Contemporary Revolutions And Political Transformations: Their Role In Enhancing Sustainable Development (Journal of the College of Basic Education, 2026)
The Arab world has witnessed profound political transformations as a result of contemporary revolutions that erupted in the past two decades. The people aspired to freedom, social justice, and democracy. These revolutions were not limited to political demands alone but were also the result of accumulated economic and social challenges over the years. This research aimed to study the impact of contemporary revolutions on sustainable development.Contemporary RevolutionsSustainable DevelopmentPost-Revolution Challenges